Web-based Cyber Counseling to Improve Students’ Counseling Interests - Prasetya, Angga Dwi; Sugiyo, Sugiyo; Japar, Muhammad (Jurnal Bimbingan Konseling)
This study attempted to improve students? counseling interests by using a Web medium in form of Cyber Counseling. To achieve such purpose, this study employed one group pre-test post-test design. Meanwhile, the instrument used to collect the data was counseling interest scale. The subjects of this study were 6 students chosen by purposive sampling technique. The researchers analyzed their data by using wilcoxon non-parametric analysis. The results showed that web-based Cyber Counseling effectively improved students? counseling interests (Z= -2.226, p < 0.05). This result asserts that Cyber Counseling has an implication toward the optimization of counselors? roles and professionalism in the utilization of Cyber Counseling for the development of Information and Technology resources development.